Internationalization of Higher Education in Post-Soviet Ukraine - Kushnarenko, Valentyna; Knutson, Sonja (International Higher Education, 2014)
Internationalization of Ukrainian higher education is becoming an important topic of discussion at national and institutional levels. Ukrainian universities consider internationalization as a major tool to impel much needed internal change and improve access to knowledge, research and funding across borders. Ukrainian students view international opportunities as critical to succeed in the European job market. Ukraine, an ex-USSR republic, which borders NATO and the European Union countries on the West and Russia on the East, maintains a semi-peripheral position in the international knowledge system. It tries to locate its own niche internationally and still hesitates about which developmental trajectory to follow. This paper investigates how Ukrainian universities approach the development of international outreach capacity in order to interact with potential partners on student/faculty international mobility, curriculum development, joint/dual degree initiatives, etc. Disproportionate distribution of already scarce resources, the role of historical preference towards cross-border and linguistic inclinations, and current active protests against the state government’s decision to stop the preparation process for an EU agreement emerge as important factors to shape the current Ukrainian higher education internationalization agenda.